Using Participatory System Dynamics Modeling to Examine the Local HIV Test and Treatment Care Continuum in Order to Reduce Community Viral Load. Issue 3 (20th November 2017) - Weeks, Margaret R.; Li, Jianghong; Lounsbury, David; Green, Helena Danielle; Abbott, Maryann; Berman, Marcie; Rohena, Lucy; Gonzalez, Rosely; Lang, Shawn; Mosher, Heather
Highlights: Participatory system dynamics modeling helps improve the HIV service system to reduce the epidemic. We engaged local stakeholders to critique their HIV service system using system dynamics modeling. Participants showed enhanced communication and consensus about systems understanding and solutions. Abstract: Achieving community‐level goals to eliminate the HIV epidemic requires coordinated efforts through community consortia with a common purpose to examine and critique their own HIV testing and treatment (T&T) care system and build effective tools to guide their efforts to improve it. Participatory system dynamics (SD) modeling offers conceptual, methodological, and analytical tools to engage diverse stakeholders in systems conceptualization and visual mapping of dynamics that undermine community‐level health outcomes and identify those that can be leveraged for systems improvement. We recruited and engaged a 25‐member multi‐stakeholder Task Force, whose members provide or utilize HIV‐related services, to participate in SD modeling to examine and address problems of their local HIV T&T service system. Findings from the iterative model building sessions indicated Task Force members' increasingly complex understanding of the local HIV care system and demonstrated their improved capacity to visualize and critique multiple models of the HIV T&T service system and identify areas of potential leverage. Findings also showed members' enhanced communication and consensus in seeking deeper systems understanding and options for solutions. We discuss implications of using these visual SD models for subsequent simulation modeling of the T&T system and for other community applications to improve system effectiveness.